Corporate Reputation in the Business Ethics Field: Its Relation with Corporate Identity, Corporate Image, and Corporate Social Responsibility. Issue 4 (November 2016) - Leiva, Ricardo; Ferrero, Ignacio; Calderón, Reyes
Abstract Among other reasons, corporate reputation (CR) has become a crucial management topic due to the last global financial and economic crisis and the increasing number of corporate scandals. Given its interdisciplinary character and intangible nature, CR has been a prominent issue in many disciplines, but its presence in the business ethics field has been considered scarce although it had not been measured properly, until now. With this paper, we measure the relevance of the corporate reputation construct in the business ethics field through a bibliometric analysis of the top business ethics journals over a recent 10-year period. The bibliometric analysis allowed us (a) to weigh exactly the prominence of the CR construct in the business ethics field, (b) to count the most referenced authors in the discipline, and (c) to rank the most influential papers and books dealing with the corporate reputation construct in this field. It also permitted us to conclude that the corporate social responsibility construct was the most repeated proxy of corporate reputation in business ethics, implying that for the business scholars the consequence of acting well should be and is supposed to be a good and positive evaluation by stakeholders. Other implications and comparisons with the treatment of the corporate reputation construct in the overall business literature are discussed.